Supervisor Feedback and Innovative Work Behavior: The Mediating Roles of Trust in Supervisor and Affective Commitment - Bak, HyeonUk (Frontiers in Psychology, 2020)
This study aimed to explore how the mechanisms of supervisor feedback affect innovative work behavior among local government employees and to examine the mediating roles of trust in supervisor and affective commitment, using organizational support theory and social exchange theory. The results from a cross-sectional study based on a sample of 1,699 local government employees from 65 local governments indicated that supervisor feedback had a direct effect on innovative work behavior. Trust in supervisor and affective commitment significantly mediated the relationship between supervisor feedback and innovative work behavior. The findings of this study contribute to an advanced understanding of the supervisor feedback-innovative work behavior relationship by testing the mediation model in the local government context.